1998
DOI: 10.1007/bf01280327
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin isoform usage in maize microtubules

Abstract: Summary. Antibodies specific to two of the maize ~-tubulin isoforms and to the three subfamilies of maize ct-tubulins were used in immunofluorescence microscopy to determine where and into which microtubule (MT) arrays these tubulin isoforms are incorporated in maize plants. All the tubulins examined appear to be incorporated into MTs in at least some cell types, with the possible exception of subfamily II c~-tubulins, which have been found only in the form of diffuse, nonfibrillar staining. Whereas the cz-tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The same could be true for MAP65-9, which is specific to stamens and pollen. This phenomenon has also been seen in the case of maize b-tubulins, where b2-tubulin is transcribed in many tissues but utilized only in male meiocytes (Eun and Wick, 1998). (3) The amount of protein is below the sensitivity of the immunofluorescence technique.…”
Section: Differential Localization Of At Map65 Isotypesmentioning
confidence: 89%
“…The same could be true for MAP65-9, which is specific to stamens and pollen. This phenomenon has also been seen in the case of maize b-tubulins, where b2-tubulin is transcribed in many tissues but utilized only in male meiocytes (Eun and Wick, 1998). (3) The amount of protein is below the sensitivity of the immunofluorescence technique.…”
Section: Differential Localization Of At Map65 Isotypesmentioning
confidence: 89%
“…Procedures were based on the method described by Eun and Wick (1998) and modified for better labeling of microtubules. At the end of lead treatment, apical 5-mm segments of primary roots were excised under a fixative containing 3.8% (w/v) paraformaldehyde, 10% (v/v) dimethyl sulfoxide, 0.1% (v/v) Triton X-100, 5 mM MgCl 2 and 5 mM EGTA prepared in 50 mM phosphate buffer.…”
Section: Fixation and Cryosectioning For Labeling Microtubulesmentioning
confidence: 99%
“…The expression of certain a-tubulin genes is tissue specific in maize (Montoliu et al 1989;Joyce et al 1992;Uribe et al 1998), as well in other plants (Ludwig et al 1988;Carpenter et al 1992;Kopczak et al 1992;Dixon et al 1994;Hellmann and Wernicke 1998;Schro¨der et al 2001). Immunofluorescence microscopy showed that all the isoforms of maize a-and b-tubulins examined appear to be incorporated into MTs to various extents (Eun and Wick 1998).…”
Section: Introductionmentioning
confidence: 99%